Influence of Ocean Acidification and Deep Water Upwelling on Oligotrophic Plankton Communities in the Subtropical North Atlantic: Insights from an In situ Mesocosm Study - Taucher, Jan; Bach, Lennart T.; Boxhammer, Tim; Nauendorf, Alice; , The Gran Canaria KOSMOS Consortium; Achterberg, Eric P.; Algueró-Muñiz, María; Arístegui, Javier; Czerny, Jan; Esposito, Mario; Guan, Wanchun; Haunost, Mathias; et al. (Frontiers in Marine Science, 2017)
Oceanic uptake of anthropogenic carbon dioxide (CO2) causes pronounced shifts in marine carbonate chemistry and a decrease in seawater pH. Increasing evidence indicates that these changes – summarized by the term ocean acidification (OA) – can significantly affect marine food webs and biogeochemical cycles. However, current scientific knowledge is largely based on laboratory experiments with single species and artificial boundary conditions, whereas studies of natural plankton communities are still relatively rare. Moreover, the few existing community-level studies were mostly conducted in rather eutrophic environments, while less attention has been paid to oligotrophic systems such as the subtropical ocean gyres. Here we report from a recent in situ mesocosm experiment off the coast of Gran Canaria in the eastern subtropical North Atlantic, where we investigated the influence of OA on the ecology and biogeochemistry of plankton communities in oligotrophic waters under close-to-natural conditions. This paper is the first in this Research Topic of Frontiers in Marine Biogeochemistry and provides (1) a detailed overview of the experimental design and important events during our mesocosm campaign, and (2) first insights into the ecological responses of plankton communities to simulated OA over the course of the 62-day experiment. One particular scientific objective of our mesocosm experiment was to investigate how OA impacts might differ between oligotrophic conditions and phases of high biological productivity, which regularly occur in response to upwelling of nutrient-rich deep water in the study region. Therefore, we specifically developed a deep water collection system that allowed us to obtain ~85 m3 of seawater from ~650 m depth. Thereby, we replaced ~20% of each mesocosm's volume with deep water, and thus successfully simulated a deep water upwelling event that induced a pronounced plankton bloom. Our study revealed significant effects of OA on the entire food web, leading to a restructuring of plankton communities that emerged during the oligotrophic phase, and was further amplified during the bloom that developed in response to deep water addition. Such CO2-related shifts in plankton community composition could have consequences for ecosystem productivity, biomass transfer to higher trophic levels, and biogeochemical element cycling of oligotrophic ocean regions.